Elucidating the role of mind–body connection profiles in emotional reactivity and regulation amongst typically developed adults - Kristen Van Bael; Jessica Scarfo; Emra Suleyman; Michelle Ball (BMC Psychology)
Abstract Background Adaptive emotional functioning necessitates a strong mind–body connection. The 13-item Body-Mind Connection Questionnaire (BMCQ) was developed to measure attention directed to sensations (Interoceptive Attention), identifying and describing sensations associated with emotions (Sensation-Emotion Articulation), and beliefs regarding mind–body integration and wellbeing (Body-Mind Values). This study aimed to (1) confirm and refine the BMCQ in a new sample of typically developed adults through confirmatory factor analysis (CFA), (2) identify distinct mind–body connection profiles through latent profile analysis (LPA), and (3) explore the impact of these profiles on emotional reactivity and regulation. Methods Data were collected from 401 typically developed adults from English-speaking countries, registered with Inquisit, with and without self-reported psychological disorders, aged 18 to 50 (M age  = 30.62, SD age  = 7.98), who completed the BMCQ and the Multidimensional Emotion Questionnaire, assessing frequency, intensity, persistence, and regulation of positive and negative emotions, via an online survey. Results The CFA led to removal of three BMCQ items in the sample with no disorder, confirming a three-factor model with good fit (CFI: .98, TLI: .98, GFI: .97, RMSEA: .05, RMR: .08) observed, and reliable internal consistency for the scales (ɑ = 0.70 to 0.82), resulting in the BMCQ-10. LPA in the pooled sample revealed three mind–body connection profiles: Strong Mind–Body Connection, Weak Mind–Body Connection, and Mind–Body Disconnection. The Strong Mind Body Connection profile reported more frequent, intense, and persistent positive emotions and found regulating positive and negative emotions the easiest. Conversely, the Weak Mind–Body Connection profile reported less frequent, intense positive emotions, and greater regulation difficulties. The Mind–Body Disconnection profile reported the least intense positive emotions and, with a psychological disorder present, found regulating emotions easier than both the Strong and Weak profiles. Conclusions The refined BMCQ-10 holds promise as an efficient measure of salient mind–body connection constituents. Findings underscore the nuanced, significant within-group variability that exists amongst mind–body connection beliefs, emotional reactivity, and ease of regulating emotions. Targeted interventions for persons with particular mind–body connection profiles (for example, mindfulness) may be effective avenues for enhancing adaptive beliefs which may promote the cultivation of positive emotions and improve emotion regulation in clinical and non-clinical groups.